Frontispiece: Kinetically Controlled Polymorphic Superstructures of Pyrene‐Based Asymmetric Liquid Crystal Dendron: Relationship Between Hierarchical Superstructures and Photophysical Properties. Issue 36 (26th June 2018) - Park, Minwook; Kang, Dong‐Gue; Choi, Yu‐Jin; Yoon, Won‐Jin; Koo, Jahyeon; Park, Seo‐Hee; Ahn, Seokhoon; Jeong, Kwang‐Un
Abstract : Pyrene‐based asymmetric liquid crystal dendron (PD) was newly synthesized for understanding the correlation of the kinetically controlled hierarchical superstructure with its properties. Owing to the competition bewteen driving forces, PD formed stable or metastable crystalline phases depending on the cooling rate. Various techniques were utilized to reveal the mechanism at the molecular level, and some photophysical properties are also investigated. More information can be found in the Full Paper by K.‐U. Jeong et al. onpage 9015 ff.